2021
DOI: 10.1001/jamapediatrics.2020.6834
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Home-Based Parenting Intervention to Reduce Behavior Problems in Young Children

Abstract: Behavior problems are one of the most common mental health disorders in childhood and can undermine children's health, education, and employment outcomes into adulthood. There are few effective interventions for early childhood. OBJECTIVE To test the clinical effectiveness of a brief parenting intervention, the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD), in reducing behavior problems in children aged 12 to 36 months. DESIGN, SETTING, AND PARTICIPANTS The Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
4
33
1
Order By: Relevance
“…The VIPP-SD has been related to decreases in problem behavior (e.g. O'Farrelly et al, 2021) and might be related to increases in social competence, such as prosocial behavior (see Euser et al, 2016). Because the VIPP-SD intervention was not the emphasis of the current study, but could potentially influence the results, we controlled all analyses for intervention group by adding a dummy variable (0 = intervention group, 1 = control group).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The VIPP-SD has been related to decreases in problem behavior (e.g. O'Farrelly et al, 2021) and might be related to increases in social competence, such as prosocial behavior (see Euser et al, 2016). Because the VIPP-SD intervention was not the emphasis of the current study, but could potentially influence the results, we controlled all analyses for intervention group by adding a dummy variable (0 = intervention group, 1 = control group).…”
Section: Methods Participantsmentioning
confidence: 99%
“…In a pilot study focusing only on fathers the feasibility was rated high, but the pilot was too small (N = 5) for effectiveness evaluation (Lawrence et al, 2013). In the large Healthy Start, Happy Start trial the involvement of fathers seemed not to add to the effectiveness of the intervention (O'Farrelly et al, 2021). Another study showed the feasibility of prenatal video-feedback using ultrasound (VIPP-PRE) with fathers (Alyousefi-van Dijk et al, 2021).…”
Section: Future Directionsmentioning
confidence: 99%
“…Clinicians delivering the intervention attended a 5-day accredited training in the VIPP-SD programme and the VIPP-PMH adaptations, with supervision by an accredited supervisor prior to each delivered session. Sessions were audio-recorded with parental consent, and a randomly selected 10% of audio recordings were coded for fidelity by an independent researcher using a VIPP-SD adherence scale adapted for VIPP-PMH (O'Farrelly et al, 2018(O'Farrelly et al, , 2021. Scores range from 1 (did not follow the manual at all) to 5 (followed the manual very closely), with all coded sessions rated at least 3 ("acceptable fidelity").…”
Section: Interventionmentioning
confidence: 99%